2016
DOI: 10.1186/s40064-016-2714-3
|View full text |Cite|
|
Sign up to set email alerts
|

Experimental analysis and numerical simulation of bed elevation change in mountain rivers

Abstract: Studies of sediment transport problems in mountainous rivers with steep slopes are difficult due to rapid variations in flow regimes, abrupt changes in topography, etc. Sediment transport in mountainous rivers with steep slopes is a complicated subject because bed materials in mountainous rivers are often heterogeneous and contain a wide range of bed material sizes, such as gravel, cobbles, boulders, etc. This paper presents a numerical model that was developed to simulate the river morphology in mountainous r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The experiments can be carried out at a 25 Hz frequency in 1.0 minutes. Therefore, the device can record up to 1,500 data of the flow velocity per second in the V x , V y and V z directions [14,5]. Fig.3.…”
Section: Methodsmentioning
confidence: 99%
“…The experiments can be carried out at a 25 Hz frequency in 1.0 minutes. Therefore, the device can record up to 1,500 data of the flow velocity per second in the V x , V y and V z directions [14,5]. Fig.3.…”
Section: Methodsmentioning
confidence: 99%
“…Bed load in natural rivers especially in steep slope rivers is often distributed with non-uniform size (Guan et al 2016;Dang and Park, 2016b). Therefore applying a bed load transport formula with uniform particle size, the calculated results often differ by orders of magnitude.…”
Section: Sediment Transport Equationsmentioning
confidence: 99%
“…They reported that grain-size parameters have an important role on bed level variation. Dang and Park (2016b) reported that bed load in the mountain river often distributed into several different fractions and each particle size is subjected to the interaction of other particles. When non-uniform bed load is transported through channels, not only aggradation and degradation occur, but sorting also occurs in a similar way.…”
Section: Sediment Transport Equationsmentioning
confidence: 99%
See 2 more Smart Citations